2016
DOI: 10.1016/j.addbeh.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity facets in relation to tobacco use, abstinence-related problems, and cognitions in treatment-seeking smokers

Abstract: Anxiety sensitivity (AS)—fear of anxiety-related experiences—has been implicated in smoking motivation and maintenance. In a cross-sectional design, we examined AS facets (physical, cognitive, and social concerns) in relation to tobacco use, abstinence-related problems, and cognitions in 473 treatment-seeking smokers. After controlling for sex, race, age, educational attainment, hypertension status, and neuroticism, linear regression models indicated that AS physical and cognitive concerns were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 70 publications
6
19
1
1
Order By: Relevance
“…Consistent with our findings, results from Memetovic et al (2016) indicated that higher sensation seeking scores were associated with significantly higher odds of intention to use cigarettes after for covariates in a sample of eighth and ninth grade Canadian adolescents. To date, no study has examined factors associated with change in susceptibility to e-cigarette use, and research with respect to change in susceptibility to conventional cigarette use among adolescents has not examined sensation seeking as a predictor (Forrester, Biglan, Severson, & Smolkowski, 2007; Gritz et al, 2003; Weiss et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our findings, results from Memetovic et al (2016) indicated that higher sensation seeking scores were associated with significantly higher odds of intention to use cigarettes after for covariates in a sample of eighth and ninth grade Canadian adolescents. To date, no study has examined factors associated with change in susceptibility to e-cigarette use, and research with respect to change in susceptibility to conventional cigarette use among adolescents has not examined sensation seeking as a predictor (Forrester, Biglan, Severson, & Smolkowski, 2007; Gritz et al, 2003; Weiss et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…While this is the first study to date to examine the specific association between sensation seeking and susceptibility to e-cigarette use, the results from the present study support previous cross-sectional research examining the association with conventional cigarette use (Memetovic, Ratner, Gotay, & Richardson, 2016). Consistent with our findings, results from Memetovic et al (2016) indicated that higher sensation seeking scores were associated with significantly higher odds of intention to use cigarettes after for covariates in a sample of eighth and ninth grade Canadian adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…FTCD measures behavioral components of smoking, which are weakly associated to cigarette withdrawal symptoms [36]. Correlations between MNWS/MNWS-R total score/psychological symptoms subscale score and ASI-3 were moderate and consistent with [37] and with the evidence that anxiety sensitivity enhances acute nicotine withdrawal symptoms [38]. As expected, correlation coefficients between associated somatic features and ASI-3 scores were weak, since the first assesses only the physical symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Un resultado que no esperábamos fue que las puntuaciones elevadas en SA social predijeran la abstinencia. Estudios previos han relacionado esta subescala con las expectativas de reforzamiento positivo y con la creencia de que fumar mejora el confort social (Buckner y Vinci, 2013;Guillot, Leventhal, Raines, Zvolensky y Schmidt, 2016), pero todavía no se conoce bien su papel en el proceso de dejar de fumar, por lo que debe seguir profundizándose en su estudio.…”
Section: B E T Wald (1) Exp (B) I C (95%)unclassified